ANTITRUST POLICY AND PROTECTION OF UMKM: COOPERATION FOR ECONOMIC JUSTICE - Abdulloh Zakka Nabil Choir, Muhammad; Satria Rummy Angkasa, Frederic; Azzahra Firjatullah, Tertia; Kurniawati, Allya (INDONESIAN JOURNAL OF SOCIAL POLITIC AND POLICY STUDIES, 2024)
This article examines the importance of antitrust policy and the protection of Micro, Small and Medium Enterprises (MSMEs) in creating economic justice in Indonesia. MSMEs serve as the main pillar of the national economy, contributing more than 60% to the Gross Domestic Product (GDP) and absorbing around 97% of the total workforce. However, MSMEs face various challenges, such as difficulties in accessing capital, technological limitations, and monopolistic practices by large companies that hinder their growth. The implementation of Law No. 5/1999 on the Prohibition of Monopolistic Practices and Law No. 20/2008 on MSMEs is essential to create a healthy competition climate and provide necessary protection for MSMEs. Cooperation between these two policies is expected to improve access to financing, technological support, and strict law enforcement against monopolistic practices. With this cooperation, MSMEs are expected to innovate, improve competitiveness, and make a greater contribution to inclusive and sustainable economic growth. This article emphasizes the need for collaboration between government and stakeholders to ensure that all businesses, both large and small, have a fair chance to thrive in the national economy.